miRNome Expression Analysis Reveals New Players on Leprosy Immune Physiopathology - Salgado, Claudio Guedes; Pinto, Pablo; Bouth, Raquel Carvalho; Gobbo, Angélica Rita; Messias, Ana Caroline Cunha; Sandoval, Tatiana Vinasco; dos Santos, André Mauricio Ribeiro; Moreira, Fabiano Cordeiro; Vidal, Amanda Ferreira; Goulart, Luiz Ricardo; Barreto, Josafá Gonçalves; da Silva, Moisés Batista; et al. (Frontiers in Immunology, 2018)
Leprosy remains as a public health problem and its physiopathology is still not fully understood. MicroRNAs (miRNA) are small RNA non-coding that can interfere with mRNA to regulate gene expression. A few studies using DNA chip microarrays have explored the expression of miRNA in leprosy patients using a predetermined set of genes as targets, providing interesting findings regarding the regulation of immune genes. However, using a predetermined set of genes restricted the possibility of finding new miRNAs that might be involved in different mechanisms of disease. Thus, we examined the miRNome of tuberculoid (TT) and lepromatous (LL) patients using both blood and lesional biopsies from classical leprosy patients (LP) who visited the Dr. Marcello Candia Reference Unit in Sanitary Dermatology in the State of Pará and compared them with healthy subjects (HS). Using a set of tools to correlate significantly differentially expressed miRNAs with their gene targets, we identified possible interactions and networks of miRNAs that might be involved in leprosy immunophysiopathology. Using this approach, we showed that the leprosy miRNA profile in blood is distinct from that in lesional skin as well as that four main groups of genes are the targets of leprosy miRNA: 1. recognition and phagocytosis, with activation of immune effector cells, where the immunosuppressant profile of LL and immunoresponsive profile of TT are clearly affected by miRNA expression; 2. apoptosis, with supportive data for an anti-apoptotic leprosy profile based on BCL2, MCL1 and CASP8 expression; 3. Schwann cells (SC), demyelination and epithelial-mesenchymal transition (EMT), supporting a role for different developmental or differentiation gene families, such as Sox, Zeb and Hox; and 4. loss of sensation and neuropathic pain, revealing that RHOA, ROCK1, SIGMAR1, and AQP1 may be involved in the loss of sensation or leprosy pain, indicating possible new therapeutic targets. Additionally, AQP1 may also be involved in skin dryness and loss of elasticity, which are well known signs of leprosy but with unrecognized physiopathology. In sum, miRNA expression reveals new aspects of leprosy immunophysiopathology, especially on the regulation of the immune system, apoptosis, SC demyelination, EMT, and neuropathic pain.